The pathology of the lung in byssinotics. Issue 6 (December 1975) - Edwards, C; Macartney, J; Rooke, G; Ward, F
Abstract : A report of the gross and microscopic appearances in the lungs and the weights of the cardiac ventricles in 43 subjects receiving industrial benefit for byssinosis is presented. In 27 (63%) there was no significant emphysema, in 10 (23%) there were varying amounts of centrilobular emphysema, and panacinar emphysema was found in six (14%). Other changes were of non-specific nature, but most cases showed heavy black dust pigmentation, often associated with centrilobular dilatation of distal air spaces.